Anti-measles virus activity of 4-hydroxy-3-methoxy benzaldehyde (Vanillin) isolated from xylopia aethiopica (Dunal) A. rich (2023)
Xylopia aethiopica is a plant used ethnomedicinally for the treatment of several infections in Nigeria. This study was carried out to isolate the active compound(s) in Xylopia aethiopica and evaluate their anti-measles virus activity. The Dichloromethane (DCM) fraction of Xylopia aethiopica was fractionated using chromatographic techniques, which led to the isolation of a compound characterized using spectroscopic techniques, FT-IR, 1D and 2D NMR in addition to in vitro anti-measles evaluation in adsorption and post-infection inhibition assays. The isolated compound characterized as 4-Hydroxy-3-methoxy benzaldehyde (Vanillin) was active on measles virus and has minimum nontoxic dose of 10 μg with cytotoxic and inhibitory activity of CC 50 = 84.18 μg/mL, IC 50 = 0.71 μg/mL and selectivity index (SI) = 118.56 (r 2 = 0.979) and interfered with viral attachment and fusion. This is the first report of the isolation of Vanillin from Xylopia aethiopica leaf and its high antiviral activity shows it could be developed further into a promising antiviral lead compound.